Thin-film limit formalism applied to surface defect absorption - Holovský J.; Ballif C. (Optical Society of America, 2014)
The thin-film limit is derived by a nonconventional approach and equations for transmittance, reflectance and absorptance are presented in highly versatile and accurate form. In the thin-film limit the optical properties do not depend on the absorption coefficient, thickness and refractive index individually, but only on their product. We show that this formalism is applicable to the problem of ultrathin defective layer e.g. on a top of a layer of amorphous silicon. We develop a new method of direct evaluation of the surface defective layer and the bulk defects. Applying this method to amorphous silicon on glass, we show that the surface defective layer differs from bulk amorphous silicon in terms of light soaking.
Keywords: thin films; optical properties; absorption